O31 Levetiracetam monitoring in breast-milk: high inter-individual variability. Issue 6 (17th May 2019) - Dinavitser, N; Kohn, E; Berlin, M; Livne, A; Keidar, R; Ben-Nun, L; Agajani, N; Sheinberg, R; Gamsu, S; Flor-Hirsch, H; Brandriss, N; Bar-Chaim, A; et al.
Abstract : Background: Anti-epileptic drug therapy is a great challenge for the practitioners during pregnancy and lactation. Levetiracetam (LEV) is commonly prescribed to pregnant women, however, there are only few publications on its use during lactation with small number of participants. Objective: To monitor LEV levels in breast-milk of epileptic mothers treated with LEV. Methods: Breastfeeding women treated with LEV during pregnancy and after delivery were recruited. Milk sample was collected before administration of the drug and other samples were collected at time points of 1, 3, 6, 9, and 12 hours after drug administration. Breastmilk and blood LEV levels were measured using HPLC. Results: Fourteen breastfeeding women participated in the study: 9 infants were fully breastfed whereas 5 were partially breastfed. Maternal average daily dose of LEV was 2517 mg. Average infant´s age was 8 weeks (3–22w). Average infant´s weight 4368 gr (3300–7000 gr). Milk/Plasma LEV concentration ratio was 0.88 (0.23–1.1). Relative Infant Dose (RID) was 40% in partial breast feeding, and 61% in full breastfeeding. Estimated average daily dose that all infants received through milk was 158 mg/d (83–250 mg). The normalized dose for the average infant weight per day was 36 mg, which is 15% less than the maximal daily dose of LEV in infants (max. daily dose in infants 1–6 months in 42 mg/d). No adverse reactions were observed in the breastfeed infants. Conclusions: Although the RID of LEV were found to be high, no adverse reactions were observed in the infants; Nevertheless, further studies are needed to elucidate the high variability of LEV excretion into breastmilk. Disclosure(s): Nothing to disclose